Pengaruh Susunan Konduktor pada Saluran Udara Tegangan Ekstra Tinggi (SUTET) - Nizar Rosyidi AS; Edy Supriyadi; Sugianto Sugianto (Institut Sains dan Teknologi Nasional, 2023)
Abstract An effort to reduce or minimise electric field and medan magnit, a common transmission network to turn up for the conductor.But the tower transmission have some extent for environmental factors such as wind speed and construction cost to be more expensive.One of the influence of the strong electric fields magnit and the gap between its phase.How is the field of electricity and medan magnit the sutet 500 kv with this method of change the configuration of a conductor.This thesis is in the field of electricity and the horizontal magnit on the configuration, delta and vertical.The simulation done by the gap between fasanya on the configuration.From the calculation shows that if the distance between the phase changes made from 12 meters to 4.9 meters at the point of the review (0), then the magnetic flux density (B) it decreased from 6.83.10-6 be 1.58.10-6 tesla (horizontal configuration), the (delta configuration) decline of 5.9 .10-6 be 3.87.10-6 tesla tesla, and for (vertical configuration) penurunanannya of 1.12.10-5 be 6.8.10-6 tesla.While the results of the calculation of the electric field strength (E) by changing the distance between the phase from 12 meters to 4.9 meters at the point of the review (0), then there is a decrease in the electric field strength of 2.97 (kV / m) to 1.87 (kV / m) with (horizontal configuration), a decrease of 1.82 (kV / m) to 1.36 (kV / m) (vertical configuration).Likewise for delta configuration when the shortened distance between its phase, then the value of the electric field strength decreases from 0.949 (kV / m) to 0.769 (kV / m).Methods for calculating the linear regression on the delta configuration, vertical configuration, and horizontal slope (+) means that the greater the distance between the phase value of B and E increases.The resulting plot of magnetic flux density with distance between phases, the optimum value of the distance between the phase (δ) of 6.7 meters and the magnetic flux density (B) 8.03.10-6 (Tesla). While the electric field strength (E) 2.2 (kV / m). Method optimum value calculation results of electric field strength and magnetic flux density meet the standards set by WHO. Keywords: strong electric field, magnetic flux density, the distance between the phase and configuration